Predictors of Knowledge of Human Papillomavirus Infection and Its Related Diseases: A Study of Women in a Nigerian Tertiary Institution - A. Okunowo, Adeyemi; O. Gabriel-Raji, Fadekemi; Yusuf-Awesu, Salimat A.; O. Salawu-Giwa, Rukayat; E. Familusi, Oluwaseun (Asian Pacific Journal of Cancer Care, 2022)
Background: The burden of HPV infection and its diseases is very high in Sub-Saharan Africa and unfortunately many vulnerable women in this region have little or no knowledge about the infection and its diseases. Bearing in mind the vital role knowledge plays in disease prevention and control, our study aimed to assess women’s knowledge about relevant aspects of human papillomavirus (HPV) infection & its related diseases and to predict the factors that influence their knowledge. Material and methods: A cross-sectional study conducted among 500 women attending a tertiary health institution in Nigeria using a self-administered structured questionnaire to assess knowledge about HPV infection, its related diseases and associated risk factors. Knowledge scores were derived, participants were categorized into having either good or poor knowledge and factors associated with good knowledge were assessed. Data was analyzed was using Statistical Package for Social Sciences version 23.0. Results: The knowledge of HPV infection & its diseases was poor with only 26.3% (123/468) of participants having good level of knowledge. Worse still, only 21.4% believed that they were at risk of acquiring the infection. Tertiary education (AOR=2.40, CI=1.30-4.44, P=0.005), low parity (AOR=4.22, CI=1.40-12.66, P=0.011), and having electronic media (AOR=6.06, CI=2.86-12.9, P<0.001), print media (AOR=4.00, CI=1.21-13.16, P=0.023), healthcare professionals (HCP) (AOR=6.30, CI=3.56-11.11, P<0.001) and organized program (AOR=13.16, CI=5.08-34.48, P<0.001) as primary sources of information significantly predicted good knowledge of HPV infection & its related diseases. Conclusion: Knowledge of HPV infection and its related diseases is very low among Nigerian women in our study. Tertiary education, low parity and having electronic media, print media, HCP and organized health programs as primary sources of information significantly predicted of good knowledge. Health education through these information channels may help to bridge the gap in knowledge and improve public knowledge about HPV and its related diseases.